Relationship between characteristics of pregnant women and thelevel of knowledge about dangers signs of pregnancy - Mantasia Mantasia; Sumarmi; Riska Nuryana; Gcinile Miky Mbukwane (UPPM STIKES Pemkab Jombang, 2025)
Danger signs of pregnancy are signs that indicate danger that could occur during pregnancy or the antenatal period, which if not detected could cause maternal death. This study aims to determine the relationship between the characteristics of pregnant women and the level of knowledge about the danger signs of pregnancy before and after education at the Barana Community Health Center in 2024. The method used in this research is a descriptive method using a cross sectional approach, namely independent and dependent variables are measured on At the same time using chi-square, the sample obtained was 30 respondents who came to the community health center and were given questionnaires and leaflets. The univariate results of the frequency of knowledge level before education were that respondents who had good knowledge were 18 (60%), while those with sufficient knowledge were 12 (40%). The level of knowledge after education was 28 (93%) respondents who had good knowledge, while 2 (7%) had sufficient knowledge. Bivariate results of knowledge level with age variable before education p-0.070, education variable p-0.053, gradivity variable p-0.511, parity variable p-0.462, employment variable p-0.064. while the level of age knowledge after education is p-0.136, the education variable is p-0.114, the gravidity variable is p-0.289, the parity variable is p-0.249, the employment variable is p-0.957. The conclusion is that the bivariate results of gravidity and employment have a relationship while the others have no relationship.